Differentiation and Function of Follicular CD8 T Cells During Human Immunodeficiency Virus Infection - Xiao, Minglu; Chen, Xiangyu; He, Ran; Ye, Lilin (Frontiers in Immunology, 2018)
The combination antiretroviral therapeutic (cART) regime effectively suppresses Human Immunodeficiency Virus (HIV) replication and prevents progression to Acquired Immunodeficiency Diseases (AIDs). However, cART is not a cure, and viral rebound will occur immediately after treatment is interrupted largely due to the long-term presence of an HIV reservoir that is composed of latently infected target cells that maintain a quiescent state or persistently produce infectious viruses. CD4 T cells that reside in B-cell follicles within lymphoid tissues, called follicular helper T cells (TFH), have been identified as a major HIV reservoir. Due to their specialized anatomical structure, HIV-specific CD8 T cells are largely insulated from this TFH reservoir. It is increasingly clear that the elimination of TFH reservoirs is a key step towards a functional cure for HIV infection. Recently, several studies have suggested that a fraction of HIV-specific CD8 T cells can differentiate into a CXCR5-expressing subset, which are able to migrate into B-cell follicles and inhibit viral replication. In this review, we discuss the differentiation and functions of this newly identified CD8 T-cell subset and propose potential strategies for purging TFH HIV reservoirs by utilizing this unique population.